Rumah Panggung, Wujud Kreativitas dari Masa ke Masa - Ketut Wiradnyana (Berkala Arkeologi Sangkhakala, 2009)
AbstractThere’s been storeyed house since prehistory, classic era and also in the traditional buildings at any ethnics in Indonesia. Till now, people in coastal area lived in storeyed house. It was people adaptation to the environment that emerged the architectural creativity with emphasized its function as a shelter.